2012
DOI: 10.1177/0040517511418557
|View full text |Cite
|
Sign up to set email alerts
|

Effect of combined flame retardant, liquid repellent and softener finishes on poly(lactic acid) (PLA) fabric performance

Abstract: The effect of flame retardant and oil/water repellent finishes on the performance and colour of poly(lactic acid) fabrics was examined, and the influence of sequential and combined finishing applications was determined. A range of drying and curing application conditions were evaluated for imparting a durable flame-retardant effect (based on a mixture of cyclic phosphonate esters) to the poly(lactic acid) fabrics. The best application conditions for applying the flame retardent with a fluorochemical and soften… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…In this test, the specimen is placed vertically in a glass column and is ignited from the top with flame progressing downward. A material with a very low LOI (i.e., around 20%) generally burns quite easily; therefore, higher LOI values corresponds better flame retardancy of a material [ 73 ]. This test is performed under the ISO 4589 standard testing method.…”
Section: Fire Testing Methodsmentioning
confidence: 99%
“…In this test, the specimen is placed vertically in a glass column and is ignited from the top with flame progressing downward. A material with a very low LOI (i.e., around 20%) generally burns quite easily; therefore, higher LOI values corresponds better flame retardancy of a material [ 73 ]. This test is performed under the ISO 4589 standard testing method.…”
Section: Fire Testing Methodsmentioning
confidence: 99%
“…Other research reported ( Cheng et al, 2016a ) that cyclic phosphonate ester improved the flame retardancy of PLA nonwovens by gas-phase mechanism, and the LOI value was increased by 33.1%, but the performance of microscale combustion and vertical burning test was not satisfactory. A mixture of phosphonate esters was used to enhance the fire performance of PLA nonwovens ( Avinc et al, 2012 ), after complex drying and curing procedure, the treated fabrics could pass the criteria of NFPA 701 after washing. The sheath/core configuration bicomponent PLA containing intumescent flame retardants were prepared by melt spinning to fabricate PLA nonwovens by thermal bonding ( Maqsood and Seide, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Avinc et al studied the effects of flame retardants and oil/water repellent finishes on the properties and color of PLA staple fabrics. It was found that the softener/lubricant used in the process has a detrimental effect on the oil recovery performance of the fabric after hot pressing [13,14,15]. Currently, most of the existing research on PLA focuses on blends of PLA and PHBV, and its woven fabrics.…”
Section: Introductionmentioning
confidence: 99%